Effect of structural properties of organosolv lignins isolated from different rice husks on their liquefaction using acidic ionic liquids - Singh, Sandip K.; Dhepe, Paresh L. (Clean Technologies and Environmental Policy, 2018)
Lignin is the only naturally available sustainable resource of aromatic compound on the Earth. Depending on the properties of lignin and the reaction conditions employed for the liquefaction, it is observed that the product distribution alters. Since ionic liquids (ILs) are considered as green and have tuneable properties, in the current work, imidazolium-based acidic ILs were employed to liquefy organosolv lignins derived from different varieties of rice husks. When liquefaction was carried out at 120 A degrees C for 1 h 36% yield for EtOAc- and DEE-soluble products with high mass balance (97 +/- 3%) was observed. The detailed characterisations of lignins and organic solvent-soluble products were done by variety of techniques [GC-MS, FT-IR, UV-Vis, 2D (HSQC) NMR], and based on this, the correlation between activity and properties of catalyst and lignin was established. Depolymerisation of organosolv lignin (derived from three rice husks) into aromatic product was done, and experimental correlation studies were performed in both.